Engagement Ceremony in the Sothern Coastal Area of Albania, An Ethno-Folkloric View - Bezo (Hasko), Blegina (European Journal of Multidisciplinary Studies, 2016)
One of the most important rituals in this area is also the engagement ceremony, which was considered like a prenuptial agreement of both young ones and it didn’t have only a moral importance but also a juridical one between both families. But this tradition had to pass through some rules that each family had to follow starting from the matchmaker who was supposed to be a respected person to the gifts that was made according to the tradition. Also, in this tradition existed some strict rules where the consanguinity of the young ones, who were going to be engaged was forbidden. The engagement was allowed only if they were cousins after seven generations had passed. This rules was to avoid problems with the baby’s health and also that the baby would be pure blood. Anyway the engagement could never be broken by the girls or the girl’s family as I was considered to be a great offense to the boy and this could bring blood feud. The engagement ceremonial started from the day that the word was given and the setting date of the day. That rings were exchanged, that happened on Monday or Thursday, which was accompanied by giving gifts. But engagement can be broken from the family of the boy only for some reasons, if the girl was sick or deterioration of relations between the families up in enmity to property issues, if separate for moral issue then the family of the boy had to give explanations for claims that they had based on facts, otherwise that was a great insult to the girl’s family amounting to enmity. A key step in this ritual is the moral and educational preparation for daughter as well for the men, and also the preparation of the girl for this holy day from the preparation and decoration of the girl from dyeing hair with henna and to the preparation of the dowry.